CURCUMA XANTHORRHIZA ROXB. IN DIGESTIVE HEALTH MANAGEMENT: A SYSTEMATIC REVIEW OF PHARMACOLOGICAL AND ETHNOMEDICAL EVIDENCE - Gladis Avika; Abdullah, Dessy (Nusantara Hasana Journal, 2025)
Curcuma xanthorrhiza Roxb. (commonly known as Temulawak) is a traditional Indonesian medicinal plant widely used for managing digestive disorders. This systematic review aims to critically evaluate the pharmacological mechanisms, clinical relevance, and ethnomedicinal applications of Curcuma xanthorrhiza in digestive health. Literature was obtained from PubMed, ScienceDirect, Scopus, Google Scholar, and Garuda from 2013 to 2023, using keywords including "Curcuma xanthorrhiza," "digestive health," "gastrointestinal disorders," "curcuminoids," and "xanthorrhizol." The included studies reveal that bioactive compounds such as curcuminoids (1.6%–2.2%) and xanthorrhizol (1.48%–1.63%) exert hepatoprotective, anti-inflammatory, antimicrobial, and carminative effects. Traditional forms include fresh herbal decoctions, powdered simplisia, and polyherbal formulas, while modern preparations involve standardized extracts. Curcuma xanthorrhiza demonstrates promising efficacy and safety for improving digestive function and modulating gastrointestinal metabolism. Its integration into clinical phytotherapy and public health strategies could provide a culturally relevant, evidence-based alternative to conventional therapy.